2019
DOI: 10.1002/biot.201800593
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Performance of Chromatographic Separations Using Microfluidics: Multiplexed and Quantitative Screening of Ligands and Target Molecules

Abstract: The optimization of chromatography ligands for the purification of biopharmaceuticals is highly demanded to meet the needs of the pharmaceutical industry. In the case of monoclonal antibodies (mAbs), synthetic ligands comprising multiple types of interactions (multimodal) provide process and economic advantages compared to protein-based affinity ligands. However, optimizing the operation window of these ligands requires the development of effective high-throughput screening platforms. Here, a novel microfluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…They claimed that their results were consistent with those obtained from a microscope or conventional chromatography system. [ 117 ] Afterward, in a 2019 publication, [ 118 ] they designed a microfluidic system composed of three individual chambers packed with different chromatography beads, such as protein A, CM Sepharose, and Q Sepharose, to determine recovery yield and purities quantitatively. Here, an artificial mixture, containing immunoglobulin G (IgG) and BSA, was used to evaluate the quantitative performance of their system.…”
Section: Microfluidic‐based Separation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They claimed that their results were consistent with those obtained from a microscope or conventional chromatography system. [ 117 ] Afterward, in a 2019 publication, [ 118 ] they designed a microfluidic system composed of three individual chambers packed with different chromatography beads, such as protein A, CM Sepharose, and Q Sepharose, to determine recovery yield and purities quantitatively. Here, an artificial mixture, containing immunoglobulin G (IgG) and BSA, was used to evaluate the quantitative performance of their system.…”
Section: Microfluidic‐based Separation Methodsmentioning
confidence: 99%
“…Compatible with the use of complex matrices such as cell culture supernatants, this technique can also be integrated with valves and optical sensors. [ 118 ]…”
Section: Microfluidic‐based Separation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study report suggested that this strategy can potentially be utilized as a predictive analytical tool in the context of purification of mAb (Pinto I. F. et al, 2019). The benefits of a HT chromatography system include its availability to predict design space for dynamic binding capacity (DBC), collect data for the prediction of elution behavior, and allow significant investigation using DoE (McDonald et al, 2016).…”
Section: High-throughput Technologiesmentioning
confidence: 99%
“…Chromatography can be categorized based on the type of ligand employed, such as ion-exchange chromatography, hydrophobic interaction chromatography, affinity chromatography, and mixed-mode chromatography. The performance of chromatography is greatly affected by the type and operating mode of ligands. , Therefore, the discovery and optimization of ligands have always been a major focus of research in chromatography development. However, the rate of discovery of new effective ligands has recently decreased. Fortunately, some studies have determined promising results by optimizing ligand operation modes. For example, the grafting of ligands to create a three-dimensional distribution has been shown to increase chromatographic adsorption capacity. , Sun and colleagues , conducted a systematic study on an anion exchanger of polyethylenimine (PEI)-grafted Sepharose FF and demonstrated enhanced adsorption capacity, effective pore diffusion, and an upgraded adsorption rate of bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%